A atividade de fiscalização de contratos de terceirização em uma Instituição Federal de Ensino Superior - Cunha, Antônia Karina Barroso Gouveia (2017)
Outsourcing services represent significant amounts in public contracting, and are essential for the Administration to carry out its final activities, providing public service to society. Thus, in order to ensure that the contracting of these services is effectively advantageous and efficient, Law 8.666/93 established that the Administration should designate a public server for the supervision and monitoring of public contracting. In the meantime, the role of prosecutor for outsourced contracts with labor assignment requires extensive knowledge of the server in relation to labor, social security and tax obligations, as well as knowledge of administrative contract, otherwise the public prosecutor may not perform an efficient, as well as not complying with normative determinations, such as Normative Ruling 02/2008/SLTI/MPOG. This qualitative-quantitative study, with an exploratory and descriptive approach, has as a general objective to present a comparative analysis of the degree of execution of the surveillance activities and the degree of importance assigned by the fiscal to the activity of surveillance of outsourcing contracts in a IFES. The theoretical approach is based on concepts of administrative contracts, their characteristics and main modalities, general notions about surveillance of contracts, surveillance activities and the responsibility of the Administration and the fiscal. As a data collection tool, a questionnaire elaborated on a Likert Scale was used, which identifies eight factors related to the surveillance activities of outsourced services contracts with assignment of labor, which was applied to outsourced fiscal servers of IFES in study. For the analysis of the quantitative data and interpretations of the results, classic methods of Descriptive Statistics were applied, already for the qualitative data, an interpretative analysis of the report of the fiscal servers was carried out. The results show that the main fragilities of the surveillance correspond to the activities of the first month of services rendered and to the activities when the contract expires. Linked to this is the need for fiscal qualification, and also to increase the number of servers assigned to the fiscal role. It is concluded, therefore, that the Administration needs to improve the conditions of work of the fiscal servers and to find ways to qualify and train these fiscal to carry out more efficient inspections and in compliance with the current legislation.